Indonesian translation. Perbandingan kinerja Quicksort dan Mergesort dalam Flutter Framework - Fahreza, Achmad; Suhartono (Jurnal Informatika dan Sains Media (JISMA), 2024)
This study provides a comparative analysis between Quicksort and Mergesort sorting algorithms in the context of the Dart programming language environment. The results show that Quicksort dominates in terms of speed when dealing with small data, while Mergesort excels when data is large. Although Mergesort is more efficient in large data size situations, it requires significant additional memory allocation, whereas Quicksort makes more efficient use of memory space. Therefore, the choice between these two algorithms becomes highly dependent on the size of the data and the terms of use. For sorting data with small sizes (under 400 elements), Quicksort is a better choice in terms of performance. On the other hand, Mergesort is recommended for large data. In addition, when utilizing cache locality becomes a priority, Quicksort becomes a more optimal choice for all data sizes.